2008 IEEE/RSJ International Conference on Intelligent Robots and Systems 2008
DOI: 10.1109/iros.2008.4651066
|View full text |Cite
|
Sign up to set email alerts
|

Combined wind speed and angle control in a virtual environment using a static observer

Abstract: Abstract-This paper develops a static observer for estimating wind speed in order to control wind speed and angle control at a user position in a submersive virtual environment. Addition of wind display evolves the Treadport Virtual environment into a highly immersive virtual environment called Treadport Active Wind Tunnel (TPAWT). Experiments on a scaled model of the TPAWT show that headwind flow stream diverges at the user. Pitot tube sensors placed at a particular region of converged flow in the scaled TPAW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Previous studies on scaled system showed promising results [6][7][8][9]. Key features of the full-scale system adapted from scaled system and the major difficulties and features that required modifications are stated below.…”
Section: Major Modifications From Scaled Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on scaled system showed promising results [6][7][8][9]. Key features of the full-scale system adapted from scaled system and the major difficulties and features that required modifications are stated below.…”
Section: Major Modifications From Scaled Modelmentioning
confidence: 99%
“…We first developed a quarter-scale two-dimensional model of the TPAWT to prototype the design approach [6][7][8][9], based on computational fluid dynamics (CFD) models and control theory. Experimentation led to controller development for wind velocity at the user position and to understanding flow dynamics inside the TPAWT environment.…”
Section: Introductionmentioning
confidence: 99%
“…European COST Action TU0801 For their part, Kulkarni et al ( [13,14]) propose a system for wind simulation, "Treadport Active Wind Tunnel", based on computational fluid dynamics and able to simulate urban wind very precisely. This device also includes radiant panels to suggest heat.…”
Section: -P2mentioning
confidence: 99%
“…In [12][13][14]20], the CFD based input-output maps are developed in terms of v TOT and v LR . Wind speed at the user is mapped based upon v TOT and wind angle is mapped in terms of v LR .…”
Section: Control Systemmentioning
confidence: 99%
“…V act and θ act are the vent speed and valve angle measured by potentiometers and pitot probes. The required vent speed is determined from the output feedback controller [12][13][14]20]. Vent speed is regulated by PI control loops that regulate the valve angles.…”
Section: Control Systemmentioning
confidence: 99%